Susceptibility Status of Aedes aegypti Mosquito (Diptera: Culicidae) to Organophosphate and Pyrethroid Insecticides in Tanjung Priok Port Health Quarantine - Yahiddin Seliandro; Tri Baskoro T Satoto; Sitti Rahmah Umniyati; Nur Alvira Pascawati (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Animal-borne diseases and vectors in seaport health areas is designated to be done in a rapid and precise manner. One of the Ae. aegypti control is using insecticides. The aims of this study are to find out and evaluate the susceptibility status of Ae. aegypti to organophosphate and pyrethroid insecticides, and also to observe the increase of non-specific esterase enzyme activities and voltage-gated sodium channel (VGSC) gene mutation in Ae. aegypti mosquitoes in Tanjung Priok Port Health Quarantine working area in 2016. Susceptibility status is determined by three distinct test methods: bioassay method (Impregnated paper containing 0.8% malathion, 0.05% cypermethrin and 0.02 ppm temephos). Biochemistry method and biomolecular assay (PCR and sequencing) to identify VGSC gene mutation. Based on bioassay test using malathion, cypermethrin and temephos showed that Ae. aegypti mosquitoes from Tanjung Priok, Sunda Kelapa, and Muara Angke ports has been resistance to malathion and cypermethrin, and were still susceptible to temephos. The results of biochemical tests on Ae aegypti to organophosphates showed moderate levels of resistance and sensitivity. VGSC gene mutation was observed on sites S989P and V1016G, while site F1534 did not showed any mutation.